Prevalence and Quality of Life of Slovenian Children with Primary Nocturnal Enuresis - Katja Karničnik; Alenka Koren; Nastja Kos; Nataša Marčun Varda (International Journal of Nephrology)
Aim. To get epidemiologic data about primary nocturnal enuresis (PNE) and its influence on the quality of life of Slovenian children and adolescents and to find out the knowledge about the disorder among school population. Methods. Prospective epidemiologic study was performed in Slovenia in 2011 and supported with two questionnaires. The first questionnaire was distributed among primary school population that included 1248 children. The second questionnaire included 44 children, who have been treated for PNE in Nephrology Unit of our Department of Paediatrics. Results. PNE was diagnosed in 12.4% of children, in 11.8% of girls and in 13.0% of boys. There was evident linkage between the appearance of PNE in children and their relatives. The study showed that PNE influences the quality of life in less than half of the investigated children. Disorder restricts them mostly in relations with coevals. Knowledge about PNE among children in elementary schools was found to be insufficient. Conclusion. We found out that the prevalence of PNE in Slovenia is comparable to prevalence in other countries. More than half of children questioned in a survey think that PNE does not affect their lives significantly. General lack of knowledge about PNE is still a problem.